Royal Wales - Fisher, Deborah C., 1955- (University of Wales Press, 2010)
Covers both the royal families that existed in pre-annexation Wales and the predominantly English royal families that have ruled over Wales since medieval times, examining the changing relationships between the rulers and the ruled.